Examination of school refusal in children with normal hearing and hearing loss - Iclal San; Aysenur Aykul Yagcıoglu; Dilek Soyler (The Egyptian Journal of Otolaryngology)
Abstract Objectives School refusal is a situation in which school-age children experience school attendance problems due to various emotional problems. This study aims to investigate the risk of school refusal in middle/high school students with and without hearing loss according to different sociodemographic variables. Methods The study was carried out by applying the “School Refusal Assessment Scale” to 90 hearing-loss and 90 normal-hearing children aged 10–18. Results In the analysis of school refusal scale scores, a highly significant difference was found between children with hearing and hearing loss. The risk of school refusal was found to be lower for students who received auditory rehabilitation, individual and group education, received education for 4 years or more, and used bilateral cochlear implants. Conclusion The results suggested that the problems experienced by children with hearing loss in language and speech skills as well as academic skills are a factor in the risk of school refusal. It is thought that it is necessary to evaluate school-age children with hearing loss in terms of school refusal and to develop strategies for intervention. To our knowledge, this is the first study to examine school refusal in children with hearing loss.